2007
DOI: 10.1379/csc-229r.1
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induces an apoptotic response in sea urchin embryos

Abstract: Cadmium is a heavy metal toxic for living organisms even at low concentrations. It does not have any biological role, and since it is a permanent metal ion, it is accumulated by many organisms. In the present paper we have studied the apoptotic effects of continuous exposure to subacute/sublethal cadmium concentrations on a model system: Paracentrotus lividus embryos. We demonstrated, by atomic absorption spectrometry, that the intracellular amount of metal increased during exposure time. We found, using termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…In contrast, if the Cd insult is much higher (i.e., 1 mM lasting 24 h), the killed cells are more numerous and, after the Cd removal, the normal development cannot be restored (Roccheri et al 2004;Agnello et al 2007). A further study showed for the first time the induction of autophagy that displays a maximum peak after 18 h of Cd exposure, when apoptosis is just beginning.…”
Section: Autophagy As a Defense Strategy In Sea Urchin Embryomentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, if the Cd insult is much higher (i.e., 1 mM lasting 24 h), the killed cells are more numerous and, after the Cd removal, the normal development cannot be restored (Roccheri et al 2004;Agnello et al 2007). A further study showed for the first time the induction of autophagy that displays a maximum peak after 18 h of Cd exposure, when apoptosis is just beginning.…”
Section: Autophagy As a Defense Strategy In Sea Urchin Embryomentioning
confidence: 95%
“…These researches indicated that the exposure of the developing embryo to subacute/sublethal concentrations of Cd induce, firstly, the activation of the early defense mechanisms, such as the synthesis of HSPs and metallothioneins (Russo et al 2003;Roccheri et al 2004), but if this is not sufficient to safeguard the developmental program, embryos will trigger the autophagic and/or apoptotic processes (Chiarelli et al 2011;Agnello et al 2007). Some of the pathways activated in sea urchin P. lividus embryos, showed in Table 1, can be occur in tandem or in sequence.…”
Section: Autophagy As a Defense Strategy In Sea Urchin Embryomentioning
confidence: 99%
“…The authors found that 9 hours of cadmium exposure were required to induce the synthesis of HSPs 70 and 72, while at least 15 hours were needed to observe the induction of hsp56 and 25kDa synthesis. In addition, it has been demonstrated that a long-lasting exposure (over 24 hours) triggers DNA fragmentation and causes the activation of caspase-3, one of the key molecules promoting apoptosis, which increased in a time-dependent way (Agnello et al 2006(Agnello et al , 2007. In sea urchin embryos, apoptosis is an important part of the defence strategy, both in physiological or stress conditions (Agnello & Roccheri, 2010).…”
Section: Sea Urchin Embryos As An In Vivo Model For the Assessment Ofmentioning
confidence: 99%
“…A xenobiotic able to cause a strong activation of all embryonic defence mechanisms reported in (Figure 3) is cadmium, an heavy metal [47,[50][51][52][53]. It must be underlined that such defence mechanisms are basally activated in physiological conditions and that their extent highly increases in stress conditions.…”
Section: Defence Mechanisms: a Success Guarantee!mentioning
confidence: 99%